Protein composition of interband regions in polytene and cell line chromosomes of Drosophila melanogaster - Demakov, Sergey A (BioMed Central, 2011)
BACKGROUND: Despite many efforts, little is known about distribution and interactions of chromatin proteins which contribute to the specificity of chromomeric organization of interphase chromosomes. To address this issue, we used publicly available datasets from several recent Drosophila genome-wide mapping and annotation projects, in particular, those from modENCODE project, and compared molecular organization of 13 interband regions which were accurately mapped previously. RESULTS: Here we demonstrate that in interphase chromosomes of Drosophila cell lines, the interband regions are enriched for a specific set of proteins generally characteristic of the "open" chromatin (RNA polymerase II, CHRIZ (CHRO), BEAF-32, BRE1, dMI-2, GAF, NURF301, WDS and TRX). These regions also display reduced nucleosome density, histone H1 depletion and pronounced enrichment for ORC2, a pre-replication complex component. Within the 13 interband regions analyzed, most were around 3-4 kb long, particularly those where many of said protein features were present. We estimate there are about 3500 regions with similar properties in chromosomes of D. melanogaster cell lines, which fits quite well the number of cytologically observed interbands in salivary gland polytene chromosomes. CONCLUSIONS: Our observations suggest strikingly similar organization of interband chromatin in polytene chromosomes and in chromosomes from cell lines thereby reflecting the existence of a universal principle of interphase chromosome organization.